Debug Your Bugs – How NLRs Shape Intestinal Host-Microbe Interactions - Rosenstiel, Philip; Lipinski, Simone (Frontiers in Immunology, 2013)
The host’s ability to discriminate friend and foe and to establish a precise homeostasis with its associated microbiota is crucial for its survival and fitness. Among the mediators of intestinal host-microbe interactions, NOD-like receptor (NLR) proteins take center stage. They are present in the epithelial lining and innate immune cells that constantly monitor microbial activities at the intestinal barrier. Dysfunctional NLRs predispose to intestinal inflammation as well as sensitization to extra-intestinal immune-mediated diseases and are linked to the alteration of microbial communities. Here, we review advances in our understanding of their reciprocal relationship in the regulation of intestinal homeostasis and implications for intestinal health.